Environmental governance the case of San Pedro Bay - Mangada, Ladylyn L. (Danyag :the UPV journal of humanities and social sciences, 2004)
The Fisheries Sector Program of the Bureau of Fisheries and Aquatic Resources reported a critical coastal resource in San Pedro Bay due to enforcement failure and lack of support from the communities in the early 90's. To arrest this reversal, government instituted the Fisheries Resource Management Program where key roles are being performed by the NGO such as developing communities as stakeholders in planning and implementation, facilitating the sustainability of programs, and local capability building. This paper discussed policy and institutional constraints that impede the sustainability and effective implementation of this program. Managing the fishery resources, as this study has shown is not anchored solely on fishery law enforcement. Dedicated sectoral interventions are also critical particularly in the fields of sustained education and skills development. This is necessary to make them fully understand ecological issues and take collective action, to set the minimum and maximum index of functionality of local structures such as the Barangay Fisheries Aquatic Resource Management Councils, Fishery Law Enforcement Team, the fisherman's association and cooperatives as well as the San Pedro Bay Council,and to enable them to secure their rights to equitable access to assets. Based on the governance framework in protecting the seas, the local government units will have to abandon its outmoded and old ways of doing things. They have to welcome partnerships and participation to generate social capital and sustainability.